2013
DOI: 10.1590/s0100-204x2013001100010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological attributes of a lowland soil affected by land leveling

Abstract: -The objective of this work was to evaluate the relationship between soil chemical and biological attributes and the magnitude of cuts and fills after the land leveling process of a lowland soil. Soil samples were collected from the 0-0.20 m layer, before and after leveling, on a 100 point grid established in the experimental area, to evaluate chemical attributes and soil microbial biomass carbon (MBC). Leveling operations altered the magnitude of soil chemical and biological attributes. Values of Ca, Mg, S, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…Water is the carrier of soil salt, and flooding treatment has a significant impact on EC. The leveling and merging of land and various field management measures are all considered important factors stimulating the soil micro-ecological changes in the conversion of dryland to paddy [25,46]. Brye et al reported a major change in soil physicochemical properties as a result of land consolidation, consistent with our results [13].…”
Section: Impact Of Conversion Of Dryland To Paddy On Soil Eco-environsupporting
confidence: 91%
“…Water is the carrier of soil salt, and flooding treatment has a significant impact on EC. The leveling and merging of land and various field management measures are all considered important factors stimulating the soil micro-ecological changes in the conversion of dryland to paddy [25,46]. Brye et al reported a major change in soil physicochemical properties as a result of land consolidation, consistent with our results [13].…”
Section: Impact Of Conversion Of Dryland To Paddy On Soil Eco-environsupporting
confidence: 91%
“…Soil nutrients are influenced by both human and natural factors. It is generally considered that with the increase in land-leveling practices, SOM, N, P, and K will decrease at first, and then increase, so fertility will decline, but only in the short-term [28,31,72]. The field investigations in this study also found that land leveling had significant negative effects on soil properties and crop growth in the short term, which is consistent with previous research results [20,30,67].…”
Section: Variability Of Soil Properties Under Different Land-levelingsupporting
confidence: 90%
“…Previous studies also reported that soil environment was unstable in a short time after land consolidation [48][49][50][51]. Generally, with the extension of land consolidation period, the microbial diversity increases gradually, but the diversity decreases in the short term after the consolidation [52][53][54][55]. Meanwhile, soil microorganisms have a certain selective adaptability to soil environment.…”
Section: Changes In Microbial Community Structure After Dryland-to-pamentioning
confidence: 93%